Evaluation the synergistic interactions between Ascorbic acid and antibiotics against Pseudomonas aeruginosa isolated from different clinical infections (Eurasian Medical Research Periodical, 2023)
The present study was carried out to shed light upon some materials that worked in increasing antibiotic activity against Pseudomonas aeruginosa. Two hundred and twelve samples including wound swab (70), ear swab (53), urine samples (41), burn swab (33), respiratory tract swab (15) were collected from different hospitals and private clinics in Wasit province during the period from the mid of October 2022 to the end-April 2023. Antibiotic susceptibility test was conducted for 54 bacterial isolates of Pseudomonas aeruginosa, tested by disc diffusion method using (12) antibiotics and the results showed a different percentage of resistance to each antibiotic as (Gentamycin, amikacin, ampicillin, bacitracin, Ciprofloxacin, Norfloxacin, chloramphenicol, erythromycin, tetracycline, streptomycin, tobramycin, Trimethoprim sulfamethoxazole). The results revealed that Ciprofloxacin was the most effective antibiotic against bacterial isolates followed by amikacin and then by Norfloxacin, and the isolates are completely resistant to both erythromycin and tetracycline. Twelve isolates were selected to detect the effect of ascorbic acid when was combined with antibiotics and tested by using disk diffusion assay. Various concentrations of the ascorbic acid were used, starting from (1 to 22.2 mg). The results showed that there is a synergistic interaction between Ascorbic acid and most of the antibiotics, Also, the synergistic effect increases with increasing concentration of the Ascorbic acid. The antibiotic chloramphenicol had the greatest effect, as the area of inhibition increased in 11 out of 12 isolates. Also, the tests showed that ascorbic acid had an antagonistic effect on some antibiotics such as norfloxacin and tobramycin, where the inhibition area decreased in 9 and 8 isolates, respectively